Lithium extraction in the municipalities of Itinga and Araçuaí in the Jequitinhonha Valley in Minas Gerais (Research, Society and Development, 2020)
Lithium is an extremely light metal with important physical and electrochemical properties. Due to its high specific heat is used in applications involving heat transfer and its high electrochemical potential and high energy density makes it highly used in batteries. As a result of its high reactivity it is not found in its elemental form in nature. Its occurrence occurs mainly in Lithium Brines and Pegmatites. In Brazil its occurrence occurs only in pegmatite deposits, being the main deposits located in the municipalities of Itinga and Araçuaí, in the Jequitinhonha Valley, Minas Gerais. The present work aims to gather information, through a literature review, about the exploration of lithium minerals in the referred municipalities. With the steady increase in demand for lithium minerals for use in technological systems, especially lithium batteries, this has led to large investments in research and infrastructure in the region, which may increase as domestic and international market demand increases. The importance of Jequitinhonha Valley in the scenario of technological development, driven by Brazil's Industry 4.0, was evident.